EFFECT OF USING FLIPPED CLASSROOM FOR TEACHING WRITING BASED ON STUDENTS' MOTIVATION: A QUASI-EXPERIMENTAL RESEARCH - Widi Andewi; Tommy Hastomo (Premise: Journal of English Education and Applied Linguistics, 2022)
The flipped Classroom is an approach that has been often mentioned in recent years, namely a learning model in which pedagogical concepts are reversed that can reorganize students' needs to ensemble the times in the modern era. This research aimed to analyze: (1) Does Flipped Classroom have better effectiveness than the Conventional Learning Model for teaching writing?; (2) Do high-motivation students show better writing competencies than low-motivation students?; (3) Is there any relationship between the learning model and students' motivation for conducting writing subject? Institut Teknologi & Bisnis Bakti Nusantara is the research location in this quasi-experimental study. The researchers employed two classes in this study: control and experimental classes. This research has 48 students as the sample of study in which each class consists of 24 students in both classes. The writing test and motivation questionnaire were employed for collecting the data as the research instrument. Before utilizing the Tukey test to identify the significance of different pairs of group means, the researchers conducted a 2x2 Multifactor Analysis of Variance for data analysis. The research findings unraveled the mean scores of F1M1 70, F1M2 75, F2M1 68, and F2M2 69. This finding concludes that (1) Flipped Classroom offers better effectiveness than the conventional learning model to teach writing, (2) The are differences in writing scores by students who have low motivation and high motivation, (3) There are interactions of learning model and student's motivation for teaching writing. Therefore, this research is expected to provide implications for implementing Flipped Classrooms with LMS for teaching English in higher education institutions in Indonesia to encourage the improvement of the flipped-classroom learning model on a larger scale.